2014
DOI: 10.1136/emermed-2014-203798
|View full text |Cite
|
Sign up to set email alerts
|

HEART score and clinical gestalt have similar diagnostic accuracy for diagnosing ACS in an unselected population of patients with chest pain presenting in the ED

Abstract: Our study demonstrates that HEART score and clinical gestalt have similar diagnostic accuracy for diagnosing ACS in an unselected population of patients with chest pain presenting in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 27 publications
3
42
2
Order By: Relevance
“…Previous studies have demonstrated that clinician gestalt alone is insufficient or not superior for identifying patients who are safe to discharge from the ED . However, the unstructured assessment used in these studies is generally a scale or an impression code of ACS probability completed based on history, symptoms, and physical examination performed by physicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that clinician gestalt alone is insufficient or not superior for identifying patients who are safe to discharge from the ED . However, the unstructured assessment used in these studies is generally a scale or an impression code of ACS probability completed based on history, symptoms, and physical examination performed by physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Only the change in cTn over time is considered. Therefore, it remains controversial whether simple, structured risk tools can surpass real, complex judgments …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary end point of the HEART score is a composite of: acute myocardial infarction (AMI), percutaneous coronary intervention (PCI), coronary artery bypass graft (CABG)surgery and death, all occurring within 6 weeks, together called MACE. These outcomes are typically related to an ACS and therefore considered indirect proof of the diagnosis 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The two most commonly used scores are the Global Registry in Acute Coronary Events 6 and the Thrombolysis in Myocardial Infarction (TIMI) 7,8 .…”
Section: Introductionmentioning
confidence: 99%